STRATEGI TRANSFORMASI DIGITAL PT HAKHARA AKADEMIA INDONESIA: ANALISIS KESENJANGAN KONDISI KINI DAN KONDISI SASARAN - Muhammad Firjatullah Nur Akbar; Hayatul Khairul Rahmat (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2026)
Most digital maturity models are built for large manufacturers and stop at assigning a score without producing actionable strategic output, which is precisely what resource-constrained service firms need. This study formulates a digital transformation strategy for PT Hakhara Akademia Indonesia through gap analysis between current and target states. A descriptive qualitative single case study assessed five dimensions across nineteen indicators on a five-level maturity scale, drawing on in-depth interviews with ten informants, document review, and three weeks of direct observation, triangulated to set each indicator value. Target state was agreed in a workshop and dimension weights derived from pairwise comparison with a consistency ratio of 0.051. Weighted maturity stood at 2.37 against a target of 3.80. Technology and infrastructure scored highest at 2.75 while data and analytics scored lowest at 1.80, so the binding constraint is governance rather than technology. Weighting reordered priorities, placing digital strategy and leadership first, and a three-stage roadmap with interim maturity targets is proposed.